Early improvement of nailfold videocapillaroscopy abnormalities in dermatomyositis patients with anti‐NXP‐2 antibody - Naoki Mugii; Yasuhito Hamaguchi; Natsumi Fushida; Motoki Horii; Tasuku Kitano; Ko Fujii; Kaori Sawada; Kyosuke Oishi; Shintaro Maeda; Takashi Matsushita (Frontiers Media S.A., 2023)
Abstract This study aimed to evaluate long‐term changes in nailfold videocapillaroscopy (NVC) findings in dermatomyositis patients with antinuclear matrix protein 2 (NXP‐2) antibody (Ab). All four patients with anti‐NXP‐2 Ab presented irregularly enlarged and reduced capillaries and hemorrhages at the initial assessment. After disease stabilization, irregularly enlarged capillaries and hemorrhages disappeared within the mean observation period of 6 months. These early improvements were not observed in patients with anti‐TIF1 Ab. The results of this study show that long‐term changes in NVC findings should be assessed using myositis‐specific Ab information.